2013
DOI: 10.19026/rjaset.6.3557
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Elemental Composition of the Pulp, Seed and Fruit Coat of Black Velvet Tamarind (<em>Dialium guineense</em>) using Instrumental Neutron Activation Analysis

Abstract: This study sought to provide data on the mineral composition of the fruit pulp, outer coat and seed of Dialiu guineense in an attempt to widen the sources of minerals for the rural population of sub-Saharan Africa. The elemental composition of the pulp, seed and fruit coat of black velvet tamarind (Dialium guineense) was determined using Neutron Activation Analysis. The fruit pulp contained manganese (23.40±1.57µg/g), chlorine (205.40±37.59 µg/g), calcium (5671.00±2132.30 µg/g), sodium (332.95±8.76 µg/g) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…It is classified as a legume and belongs to the family Fabaceae (Besong et al, 2016). The whole fruits have been reported to be a good source of nutrients, micronutrients and minerals (Achoba et al, 1992;Adamu et al, 2015;Asoiro et al, n.d.;Ofosu et al, 2013;Okudu et al, 2017) and found to have antioxidant properties relevant in the treatment/management of chronic diseases (Bamikole et al, 2018). The fruit is structurally made of the seed coat (epicarp), the pulp (mesocarp) and the seed (endocarp).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is classified as a legume and belongs to the family Fabaceae (Besong et al, 2016). The whole fruits have been reported to be a good source of nutrients, micronutrients and minerals (Achoba et al, 1992;Adamu et al, 2015;Asoiro et al, n.d.;Ofosu et al, 2013;Okudu et al, 2017) and found to have antioxidant properties relevant in the treatment/management of chronic diseases (Bamikole et al, 2018). The fruit is structurally made of the seed coat (epicarp), the pulp (mesocarp) and the seed (endocarp).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit is structurally made of the seed coat (epicarp), the pulp (mesocarp) and the seed (endocarp). The mesocarp is the part eaten by humans however the endocarp and epicarp have been reported to have some nutrients and oil which can be put to use in the animal feed industry (Ofosu et al, 2013). Apart from directly eating its mesocarp, it has been used either whole or its fruit-fraction in the production of beverage drink (Adeola and Aworh, 2010), ingredient in candy making (Samakradhamrongthai and Jannu, 2021), used in the production of citric acid (Ajiboye and Sani, 2015), used for remediation (Onyia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%